Conceptual Model of Video Learning based on Project-Oriented Problem-Based Learning and Competency-Based Education for Technical and Vocational Education - Abdul Rahman, Khairul Anuar; Rozali, Mohd Zulfadli; Abu Samah, Norazrena; Abu Bakar, Mazlan; Ahmad, Nor Aziah; Gerijih, Debie Devisser; Zakariah, Siti Hajar (Journal of Technical Education and Training, 2022)
The objective of this study is to refine and validate the aspects of Project-oriented Problem-based learning (PoPBL) and Competency-based education (CBE) in the instructional video conceptual model for Technical and Vocational Education (TVE). The researcher conducted a survey study, distributing questionnaires to 39 vocational institutions across peninsular Malaysia and Sabah, to determine the compatibility of PoPBL and CBE integration in the learning video. There are 500 respondents provided feedback. To test construct accuracy and item weakness or bias based on the data obtained, researchers used exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) with AMOS 20.0 software to confirm the components based on the constructs obtained. The results indicate there are significant relationship influenced by the elements of learning content, delivery of instruction, video design and video quality. This conceptual model's four elements are critical requirements in the setting of Technical and Vocational Education (TVE) and competency-based education. The findings of this study could be utilised to guide the design of instructional videos, particularly in the TVE, as well as a tool for evaluating current instructional videos.